2009
DOI: 10.1080/13573320902809096
|View full text |Cite
|
Sign up to set email alerts
|

‘Activity choice’ and physical education in England and Wales

Abstract: This paper draws on data from a broader study, the central object of which was to explore the place of sport and physical activity in young people"s lives. More particularly, the paper reports the findings of 24 focus groups conducted with 153 15-16-year-olds in north-west England and north-east Wales in order to examine young people"s views towards activity choice in physical education (PE). In this regard, it is suggested that despite their deep-seated preferences for "traditional", games-dominated PE curric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…This argument, like many other aspects of WADA policy, is based on a highly individualized conceptualization of the elite athlete, who is presented as an asocial, The idea that athletes have a free choice about whether to participate in sport has, perhaps, some limited applicability in relation to young people who may be deciding whether or not to play sport, though even here we know that the choices of young people are heavily constrained, particularly by parents and peers (Coakley and White 1999, Smith 2006, Smith, Green and Thurston 2009. But the suggestion that elite athletes who are subject to the WADA whereabouts system can freely choose to withdraw from athletics if they dislike that system is simplistic and misleading.…”
Section: Legitimacy and Consent As Problematicmentioning
confidence: 99%
“…This argument, like many other aspects of WADA policy, is based on a highly individualized conceptualization of the elite athlete, who is presented as an asocial, The idea that athletes have a free choice about whether to participate in sport has, perhaps, some limited applicability in relation to young people who may be deciding whether or not to play sport, though even here we know that the choices of young people are heavily constrained, particularly by parents and peers (Coakley and White 1999, Smith 2006, Smith, Green and Thurston 2009. But the suggestion that elite athletes who are subject to the WADA whereabouts system can freely choose to withdraw from athletics if they dislike that system is simplistic and misleading.…”
Section: Legitimacy and Consent As Problematicmentioning
confidence: 99%
“…This same sexual division of play between women's and men's, girl's and boy's preferences has been consistently reported in the academic research (see, for example, Collins and Kay, 2003;Hargreaves, 1994Hargreaves, , 2000Penney, 2002;Scraton and Flintoff, 2002;Flintoff, 2008;Smith et al, 2009;Wellard, 2007). In the UK, the Women's Sport and Fitness Foundation and the Institute of Youth Sport, (Gorely et al, 2011) set out in detail the extent of the sexual division of play and report that ' [t]here is some evidence that many girls retain an interest in being physically active despite their progressive rejection of sport (e.g.…”
Section: The Sexual Division Of Playmentioning
confidence: 94%
“…For example, Flintoff (2008) found a 'dominance of competitive sport practices' within school sport partnerships, that 'coordinators work within an equality or difference discourse' and that there was 'little evidence of transformative praxis needed for true inclusivity'. Further, Smith, Green & Thurston (2009) investigating '[a]ctivity choice' and physical education in England and Wales found that 'restrictions (were) particularly felt amongst girls (who were) dissatisfied with over-representation of a small number of traditional team sports'. They reported responses from children including 'It was like last week, they gave us the choice of basketball and rounders and there was twenty-odd of us that wanted to do dance and they said "No, sorry" ' ('Eve'), 'Lots of us enjoy dance don't we?'…”
Section: Citizenship: Hegemonic Framementioning
confidence: 99%
“…Furthermore, in 24 focus groups conducted with one hundred and fifty three 15Á16 year-olds in north-west England and northeast Wales, Smith et al (2009) found that although the physical education teachers in the study provided their pupils with a degree of activity choice in later secondary school, many young people in the study, particularly girls and those from lower social class backgrounds, were dissatisfied with the over-representation of a small number of traditional team sports and activities in physical education.…”
Section: Introductionmentioning
confidence: 96%